O prywatyzacji form organizacji i działania jako źródłach różnorodności administracji publicznej - Strzyczkowski, Kazimierz (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Among the development trends of contemporary administration having a significant importance for the structure of public administration, decentralization and pluralization of public administration, understood as delegating public service missions to private entities, should receive special attention. The state and its administration withdraws from performing public administrative tasks by privatizing organizational units (organizational privatization) or by privatizing tasks (material privatization) performing a public service mission. The general assumption is made that the differentiating factor is the use of private law forms in public administration activity. As a result, public administration is organizationally and functionally diverse, which on the one hand creates the conditions for the selection of the most effective solutions from the point of view of achieving the objectives of public administration. However, on the other, it creates the conditions for a conflict between the obligation of the public administration to act solely for the common good and separate interests of the private entities entrusted to carry out public administration tasks.
Keywords: decentralization; structure of public administration; democratic legitimacy; private legal form of public administration; compliance